Decrease in haemoglobin in association with aneurysm volume loss after endovascular repair of abdominal aortic aneurysm - Li, Ying; Zhang, Hanxi; Sun, Zhonghua; Zheng, Jun; Xu, Shangdong; Xu, Lei; Sun, L.Z.; Li, Yu (MedReviews, 2023)
Background: Anaemia (low haemoglobin [Hb]) is well known to be associated with high mortality and adverse cardiac events following surgical treatment of abdominal aortic aneurysm (AAA). However, little is known about the relationship of AAA volume and Hb level alterations with endovascular repair of AAA. This study aimed to examine the changes in the Hb level and aneurysm volume before and after endovascular aneurysm repair (EVAR) for AAA and determine the relationship between the post-operative Hb level and the volume loss of AAA. Methods: This retrospective study reviewed patients with AAA who underwent EVAR between January 2020 and February 2021 at a tertiary medical centre. The clinical features and medical history of the patients were analysed. Alterations in the Hb level were recorded, and the AAA volume was calculated from computed tomography angiography images before and after EVAR to infer the association between the post-operative Hb level and alterations in AAA volume. Moreover, AAA volume, pre-operative Hb level and medical history were studied to identify the risk factors for anaemia 24 h after EVAR. Results: A total of 74 patients (mean age, 67 ± 7.9 years) were included in this study. The Hb level decreased significantly 24 h after EVAR, and the post-operative Hb level was negatively correlated with AAA volume loss (r = –0.252, p = 0.041). No relationship was observed between AAA volume loss and decrease in the Hb level (r = 0.072, p = 0.571) or between pre-operative AAA volume and decrease in the Hb level (r = 0.072, p = 0.566). Furthermore, 59.5% of the patients (n = 44) developed anaemia 24 h after EVAR. The odds ratio (OR) of anaemia 24 h after EVAR was 5.3 times higher in those with hypertension (OR, 5.304; 95% confidence interval [CI], 1.024–27.424) than in those without the condition. The pre-operative Hb level (or normal Hb level) was a protective factor (OR = 0.909; 95% CI, 0.853–0.969). The area under the receiver operating characteristic curve was 0.840. The post-operative Hb level declined significantly, and AAA volume loss contributed to it. Moreover, hypertension was identified to be a risk factor for anaemia 24 h after EVAR, and pre-operative Hb level was discerned to be a protective factor. Conclusions: The findings suggest that decrease in the Hb level in the early post-EVAR stage warrants the attention of surgeons, especially in patients with a history of hypertension or a low pre-operative Hb level.